Potential Gene Association Studies of Chemotherapy-Induced Cardiotoxicity: A Systematic Review and Meta-Analysis - Yang, Xinyu; Li, Guoping; Guan, Manke; Bapat, Aneesh; Dai, Qianqian; Zhong, Changming; Yang, Tao; Luo, Changyong; An, Na; Liu, Wenjing; Yang, Fan; Pan, Haie; et al. (Frontiers in Cardiovascular Medicine, 2021)
Chemotherapy is widely used in the treatment of cancer patients, but the cardiotoxicity induced by chemotherapy is still a major concern to most clinicians. Currently, genetic methods have been used to detect patients with high risk of chemotherapy-induced cardiotoxicity, and our study evaluated the correlation between genomic variants and chemotherapy-induced cardiotoxicity. The systematic literature search was performed in the PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), CBM, the Embase database, China National Knowledge Internet (CNKI) and Wanfang database from inception until June 2020. Forty-one studies were identified that examined the relationship between genetic variations and chemotherapy-induced cardiotoxicity. And these studies examined 88 different genes and 154 single nucleotide polymorphisms (SNPs). Our study indicated 6 variants obviously associated with the increased risk for chemotherapy-induced cardiotoxicity, including CYBA rs4673 (pooled odds ratio, 1.93; 95% CI, 1.13–3.30), RAC2 rs13058338 (2.05; 1.11–3.78), CYP3A5 rs776746 (2.15; 1.00–4.62) ABCC1 rs45511401 (1.46; 1.05–2.01), ABCC2 rs8187710 2.19; 1.38–3.48) and HER2-Ile655Val rs1136201 (2.48; 1.53–4.02). Although further studies are required to validate the diagnostic and prognostic roles of these 6 variants in predicting chemotherapy-induced cardiotoxicity, our study emphasizes the promising benefits of pharmacogenomic screening before chemotherapy to minimize the chemotherapy-induced cardiotoxicity.